Konstruksi Sikap Moderat Berbasis Ruang Sosial di Desa Besowo Kepung Kediri - Jauhari, Moh. Irmawan (Proceedings of Annual Conference for Muslim Scholars, 2023)
This research aims to determine local values ​​of moderate attitudes and the construction process in Besowo Village, Kepung District, Kediri Regency. This research has a qualitative approach and case study type. Data collection techniques include in-depth interviews, participant observation, and documentation studies. Data analysis techniques condensing data, presenting data, and drawing conclusions. The research results show that there are several local values ​​of moderate attitudes such as understanding each other, respecting each other, accepting each other, working together for the common good, and not interfering in the worship activities of other people. The construction process begins internally religious community, supported by village government regulations, and religious communities are always involved in social activities in Besowo Village.